1983
DOI: 10.1288/00005537-198308000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Tympanostomy tubes and otic drops

Abstract: Otic drops have been proposed as a form of prophylaxis against the otitis media which follows middle ear contamination by water in patients with tympanostomy tubes. The potential adverse effects of this form of therapy were studied in chinchillas with tympanostomy tubes; 31 chinchillas underwent bilateral tympanostomy tube insertion. Seven animals had a mixture of green dye and Cortisporin otic suspension placed in both external auditory canals 24 hours following the placement of tympanostomy tubes and were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 8 publications
1
29
2
Order By: Relevance
“…Whereas previous studies have demonstrated that the pressure in the external ear canal must exceed 10 cmH 2 O to make fluid pass through a tympanostomy tube [5], the potassium solution apparently entered the middle ear cavity through a tympanostomy tube in the present case.…”
Section: Discussioncontrasting
confidence: 73%
“…Whereas previous studies have demonstrated that the pressure in the external ear canal must exceed 10 cmH 2 O to make fluid pass through a tympanostomy tube [5], the potassium solution apparently entered the middle ear cavity through a tympanostomy tube in the present case.…”
Section: Discussioncontrasting
confidence: 73%
“…These topical preparations mostly contain an aminoglycoside antibiotic and various solvents. Ototoxic side effects of aminoglycosides are known with their systemic applications; topical ototoxicity has also been demonstrated both in animal experiments and as case reports in their clinical use (3)(4)(5). Thus, an alternative antibiotic with a lower risk of ototoxicity than aminoglycosides could find safer application.…”
Section: Introductionmentioning
confidence: 99%
“…Ceftazidime (Tazicef, Smith Kline & French Labo¬ ratories, Philadelphia, Pa) is a thirdgeneration cephalosporin antibiotic with a broad antibacterial spectrum. It is effective against many gram-posiAccepted for publication February 1,1989 tive and gram-negative organisms in¬ cluding Staphylococcus aureus, Haemophilus influenzae, Pseudomonas aeruginosa, and many other enteric organisms.6'8 As such, ceftazidime is an appropriate antimicrobial agent to in¬ vestigate as a potential ototopical an¬ tibiotic. To our knowledge, ototoxic side effects resulting from middle ear administration of ceftazidime have not been previously studied.…”
mentioning
confidence: 99%